Suicidalidade em pacientes com transtorno de pânico e agorafogia: prevalência e fatores associados - Bauer, Victor Augusto [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Introduction: Psychiatric disorders are the main risk factors for suicidal behaviors or 'suicidality', but there are few studies on this issue involving patients with anxiety disorders in general and panic disorder (PD) in particular. Most PD patients that seek treatment have agoraphobia associated to the disorder (PAD). Investigations of suicidality among PAD patients have been largely inconclusive and there are no Brazilian publications on this issue. Objectives: this study aimed to estimate the prevalence of various lifetime suicidal behaviors (feeling that life is not worth living, wishing to be dead, suicidal thoughts, plans and attempts) in PAD patients and to evaluate sociodemographic and clinical factors associated with these behaviors. Method: A cross-sectional study was conducted with a sample of adult patients presenting PAD (DSM-IV criteria) undergoing treatment in a private clinic in Bauru and in the outpatient service for anxiety and obsessive-compulsive disorders at Botucatu Medical School - São Paulo State University from January 2011 to October 2013. The assessment instruments used were: a questionnaire designed to collect sociodemographic and clinical data, the Panic and Agoraphobia Scale (PAS) to evaluate PAD clinical severity and the Mini International Neuropsychiatric Interview (M.I.N.I.) to evaluate the co-occurrence of other psychiatric disorders. Initially, the prevalence of the outcomes of interest (suicidal behaviors) was calculated; then, bivariate analyses were performed between these outcomes and several demographic and clinical variables. For the categorical explanatory variables the Chi-squared and the Fisher exact tests were used, whereas for the quantitative variables (e.g.: age, schooling years, PAS score) the Student t test (normal distribution) and the Mann-Whitney test (non-normal distribution) were used. Results: 45 patients (66.7% women and 33.3% men) were assessed. Ages ranged from 19 to 68; ...

Introdução: Os transtornos psiquiátricos são os principais fatores de risco para comportamentos suicidas ou suicidalidade, mas são relativamente escassos os estudos sobre este tema com portadores de transtornos de ansiedade em geral e transtorno de pânico (TP) em particular. A maioria dos pacientes com TP que procura tratamento apresenta agorafobia associada. Pesquisas sobre suicidalidade em pacientes com TP ainda são poucas e inconclusivas, não havendo estudos nacionais publicados sobre o tema. Objetivos: Este estudo objetivou estimar a prevalência de vários comportamentos suicidas na vida (achar que não vale a pena viver, desejar estar morto, ideação suicida, planejamento e tentativas de suicídio) em pacientes com TP e agorafobia (TPA), assim como avaliar fatores sóciodemográficos e clínicos associados à ocorrência de tais comportamentos. Método: Estudo transversal, com uma amostra clínica de conveniência de pacientes adultos (18 anos ou mais) portadores de TPA (critérios do DSM-IV) em tratamento em uma clínica privada de Bauru e no ambulatório de transtornos ansiosos e obsessivo-compulsivos (ATAOC) da Faculdade de Medicina de Botucatu-Unesp de janeiro de 2011 a outubro de 2013. Os instrumentos de avaliação utilizados foram: um questionário especialmente elaborado para obtenção de dados sociodemográficos e clínicos, a Panic and Agoraphobia Scale (PAS) para avaliar a gravidade dos sintomas de TPA e a Mini International Neuropsychiatric Interview (M.I.N.I.) para avaliar a ocorrência de comorbidades psiquiátricas. Calculou-se a prevalência de comportamentos suicidas (desfechos de interesse) e, a seguir, foram feitas análises bivariadas entre estes e diversas variáveis sociodemográficas e clínicas. Para as variáveis categóricas foi utilizado o teste de qui-quadrado ou de Fisher, quando indicado, e para variáveis quantitativas (ex. idade, anos de escolaridade, pontuação na PAS) utilizaram-se os ...
Suicidality in patients with panic disorder and agoraphobia: prevalence and associated factors
Keywords: Comportamento suicida; Suicídio; Agorafobia; Estudos transversais; Agoraphobia; Suicidal behavior